BURSTT: Bustling Universe Radio Survey Telescope in Taiwan. (26th September 2022) - Lin, Hsiu-Hsien; Lin, Kai-yang; Li, Chao-Te; Tseng, Yao-Huan; Jiang, Homin; Wang, Jen-Hung; Cheng, Jen-Chieh; Pen, Ue-Li; Chen, Ming-Tang; Chen, Pisin; Chen, Yaocheng; Goto, Tomotsugu; et al.
Abstract: Fast Radio Bursts (FRBs) are bright millisecond-duration radio transients that appear about 1000 times per day, all-sky, for a fluence threshold 5 Jy ms at 600 MHz. The FRB radio-emission physics and the compact objects involved in these events are subjects of intense and active debate. To better constrain source models, the Bustling Universe Radio Survey Telescope in Taiwan (BURSTT) is optimized to discover and localize a large sample of rare, high-fluence, and nearby FRBs. This population is the most amenable to multi-messenger and multi-wavelength follow-up, which allows a deeper understanding of source mechanisms. BURSTT will provide horizon-to-horizon sky coverage with a half power field-of-view (FoV) of ∼10 4 deg 2, a 400 MHz effective bandwidth between 300 and 800 MHz, and subarcsecond localization, which is made possible using outrigger stations that are hundreds to thousands of km from the main array. Initially, BURSTT will employ 256 antennas. After tests of various antenna designs and optimizing the system's performance, we plan to expand to 2048 antennas. We estimate that BURSTT-256 will detect and localize ∼100 bright (≥100 Jy ms) FRBs per year. Another advantage of BURSTT's large FoV and continuous operation will be its greatly enhanced monitoring of FRBs for repetition. The current lack of sensitive all-sky observations likely means that many repeating FRBs are currently cataloged as single-event FRBs.